Housing the Refugees: the Greek Experience and Its Political Pitfalls - Konstantinos Lalenis; Elias Beriatos (European Regional Science Association (ERSA), 2006)
Cultural reproduction is one of the main prerogatives to determine behavioural interaction between immigrants and their host environment. And in turn, cultural reproduction mainly develops within a framework of urban conditions, policies and substructures aimed to provide for residence, mobility and transportation, education and information, health and social services, and leisure, cultural and athletic activities. A major challenge nowadays for urban planning and urban governance is to incorporate in its processes the new dynamics created by increasing migration, and secure for immigrants all the above in an acceptable quality –that in essence is fostering their human rights. Greece has been traditionally a source of outgoing migration until early '90s, when the collapse of the neighbouring communist regimes and the destabilization of the Middle East made it a destination of migration, mainly coming through its northern and eastern borders. According to the Greek legislation, immigrants who arrived and resided in Greece since late '80s and after the collapse of the socialist states in Europe can be distinguished in two categories: the ones of Greek origin and the ones without it. And one could see a clear difference in policies aiming to accommodate the "repatriating Greeks" in their new environment, than the ones targeted to the other immigrants, the former being more in variety, more elaborated and better financed than the latter. This paper will examine the policies and projects related to providing immediate and intermediate shelter and permanent housing for the refugees, the up to now outcomes of these policies, and their repercussions for human rights of immigrants. Aim of the paper is to relate these policies to the current urban planning and governance framework –and hence to the dominant ideological and political currents and their repercussions for human rights-, to evaluate the outcomes of these policies as it concerns the effects on immigrant well-being, and to attempt conclusions for reassessment of the Greek urban planning system with an effect on immigration, seen in a broader theoretical framework covering EU, the MENA countries, and the wider Balkan area.
Keywords: 330